Penggalian Data Bengkel Untuk Basis Data Awal Aplikasi Mybengkel Menggunakan Location Based Service - Riswantoro Ikhwan H; Nugroho Agung Pambudi; Yuyun Estriyanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
Abstract: Motorcyclists and cars have difficulty finding a repair shop when it breaks down on the road, because of the lack of information on the location of the workshop around. In the end, it raises the need for vehicle users to find out information about the workshop and the location of the workshop. The purpose of this study is to present data on the operational characteristics of the workshop. This study uses a quantitative survey method. Collecting data in this study using a questionnaire with a resource person, namely the owner of the workshop. The research instrument was compiled in the form of a questionnaire that had been tested for instrument validity by experts. The results of the questionnaire data obtained from the respondents were then tabulated using Microsoft Excel into a bar chart. This study took a sample of 70 workshops in Solo Raya. The results of this study indicate that the average operating hours of workshops in Solo Raya are at 08.00 WIB. The average closing hours for workshop operations in Solo Raya is 16.00 WIB. The types of workshops are divided into 2, namely general workshops there are 62 workshops while specialist workshops have 8 workshops. The average type of workshop work that can serve consumers is light service. There are 43 mechanics who can be called out of the workshop, while 27 workshops cannot be called out. The average number of mechanics for motorcycle and car repair shops in Solo Raya is 1 and 2 mechanics. The average estimated cost of a light motorcycle service is Rp. 30,500, the average estimated service cost for motorbikes is Rp. 136,500, the average estimated cost of a light car service is Rp. 175,500, the average estimated service cost for the weight of the car is Rp. 1,987,500, the average estimated cost of motorcycle tires is Rp. 10,200, the average estimated cost of washing a motorbike is Rp. 22,500, the average estimated cost of body repair is Rp. 300,000, the average estimated cost of repairing the dynamo is Rp. 550.000, the average estimated cost of car AC service is Rp. 125,000, the average estimated cost of repairing a car radiator is Rp. 300,000, the average estimated cost of car carburetor service is Rp. 187,500, and the estimated average cost of a chassis specialist is Rp. 375,000.